“Teaching is a learning experience”:: Exploring Faculty Engagement with Low-Income Adult Learners in a College-Community Partnership Program - Bourke, Alan; Vanderveken, James; Ecker, Emily; Bell, Hayley; Richie, Kimberly (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
This article examines interview data with faculty teaching in a college-community partnership program for low-income adult students in an urban setting. The purpose of the study was to explore faculty understandings of the diverse learning needs of their students and the perceptions they have of the efficacy of their teaching practices regarding course design and delivery. Findings highlight the central dynamic of teaching as a negotiated relationship and process of mutual learning between faculty and students, and the means by which faculty work to create engaging and empowering classroom environments. Our research is relevant to educators interested in designing and delivering courses from a social justice perspective in order to encourage adults from low-income communities to pursue a post-secondary pathway. Keywords: post-secondary access, adult learners, low-income student engagement, social justice education